2000
DOI: 10.1161/01.atv.20.12.2630
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 Deficiency Reduces Atherosclerotic Lesions in Double-Knockout Mice (ApoE /− /ICAM-1 /− ) Fed a Fat or a Chow Diet

Abstract: Abstract-Intercellular adhesion molecule (ICAM)-1, a major adhesion molecule, plays a critical role in the homing of leukocytes to sites of atherosclerotic lesions. However, very little is known on the role of ICAM-1 in initiating and perpetuating vascular lesions in ApoE Ϫ/Ϫ mice fed a chow or a fat diet. This study has investigated the mean aortic lesions in mice (C57BL6 background) with a single-knockout (ApoE Ϫ/Ϫ ) or double-knockout (DKO; ApoE Ϫ/Ϫ , ICAM-1 Ϫ/Ϫ ) fed a chow or a fat diet over a period of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 54 publications
3
92
1
Order By: Relevance
“…For example, the proatherogenic effect of VCAM-1 has been demonstrated by the decreased lesion size in low density lipoprotein receptor-deficient mice containing a targeted deletion of the VCAM-1 gene (32). Similarly, ICAM-1 deficiency reduced atherosclerosis in both diet-induced (33) and apoE-deficient animals (34). The importance of MCP-1 has been demonstrated by a decrease in atherosclerosis in mice that lack either MCP-1 (35) or its receptor, CCR2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the proatherogenic effect of VCAM-1 has been demonstrated by the decreased lesion size in low density lipoprotein receptor-deficient mice containing a targeted deletion of the VCAM-1 gene (32). Similarly, ICAM-1 deficiency reduced atherosclerosis in both diet-induced (33) and apoE-deficient animals (34). The importance of MCP-1 has been demonstrated by a decrease in atherosclerosis in mice that lack either MCP-1 (35) or its receptor, CCR2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ICAM-1 in atherosclerosis has been demonstrated in apoE -/-mice deficient in ICAM-1, which had reduced lesion size (Nageh, Sandberg et al 1997). Time course analysis revealed that ICAM-1 is not only involved in the initial plaque formation but also in subsequent progression in mice (Bourdillon, Poston et al 2000;Kitagawa, Matsumoto et al 2002). These data were supported by results obtained in apoE -/-mice treated with anti-ICAM-1 neutralising antibodies (Patel, Thiagarajan et al 1998).…”
Section: Function Of Icam-1mentioning
confidence: 64%
“…85 It has been proposed that the atheroprotective effects of antibodies directed against the CD40 ligand are achieved by an inhibition of endothelial cell VCAM-1 expression. 86 The effects of reduced ICAM-1 expression are inconsistent, with both positive 87 and negative 88 results reported. Various selectins and members of the immunoglobulin superfamily also exist in a soluble plasma form in concentrations that have been shown in some studies to correlate with the presence of other cardiovascular risk factors.…”
Section: Endothelial Cell Adhesion Proteins and Chemokinesmentioning
confidence: 99%
“…85 It has been proposed that the atheroprotective effects of antibodies directed against the CD40 ligand are achieved by an inhibition of endothelial cell VCAM-1 expression. 86 The effects of reduced ICAM-1 expression are inconsistent, with both positive 87 …”
mentioning
confidence: 99%